On one approach to the discretization of the lavrent’ev method - Pereverzev, S. V.; Solodkii, S. G. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We propose a new scheme of discretization of the Lavrent’ev method for operator equations of the first kind with self-adjoint nonnegative operators of certain “smoothness.” This scheme is more economical in the sense of the amount of used discrete information as compared with traditional approaches.